2000
DOI: 10.1046/j.1523-1755.2000.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mitogen-activated protein kinase family in rat renal development

Abstract: ERK, p38, and MKP-1 are strongly expressed in developing kidney, and JNK is detected predominantly in adult kidney. Both the temporal and spatial expression of ERK coincides with the maturation of the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 18 publications
1
53
1
Order By: Relevance
“…We ourselves have previously shown the speci®city of this antibody under the same conditions by showing colocalisation of TNFa, TRAF-2 and total NF-kB staining with the active NF-kB staining and showing clear nuclear localisation of the active NF-kB (van Den Brink et al, 2000). Phosphospeci®c antibodies are also increasingly being used in immunohistochemistry in formalin ®xed, para n embedded tissue, especially pJNK and pp38 MAPK (Omori et al, 2000;Pirvola et al, 2000). Speci®city is usually con®rmed by showing results from immunoblot experiments.…”
Section: Discussionmentioning
confidence: 99%
“…We ourselves have previously shown the speci®city of this antibody under the same conditions by showing colocalisation of TNFa, TRAF-2 and total NF-kB staining with the active NF-kB staining and showing clear nuclear localisation of the active NF-kB (van Den Brink et al, 2000). Phosphospeci®c antibodies are also increasingly being used in immunohistochemistry in formalin ®xed, para n embedded tissue, especially pJNK and pp38 MAPK (Omori et al, 2000;Pirvola et al, 2000). Speci®city is usually con®rmed by showing results from immunoblot experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblot analyses of kidney homogenates, as well as immunohistochemical studies, have indicated that ERK and p38 MAPKs are predominantly expressed in the developing kidney, the highest levels being observed in the embryo (10). The role of JNK MAPK in embryogenesis has been investigated, and it has been shown that the loss of the MKK4 gene, a JNK activator, results in embryonic death (26).…”
Section: Evidence For the Role Of Mapk In Kidney Developmentmentioning
confidence: 99%
“…AII stimulates mesangial cells to produce various ECM components in cell culture studies (6), and also promotes cell proliferation and differentiation (7). It has also been shown that human fetal mesangial cells express α-SM-actin (8,9) and that large-scale cell proliferation occurs during kidney development (10). Up-regulated α-SM-actin synthesis by mesangial cells is frequently associated with increased cell proliferation and ECM production (11).…”
Section: Introductionmentioning
confidence: 99%
“…p38 MAPK and JNK signaling is evident during kidney development in the rat (8). This appears to be important in kidney development since the addition of a p38 inhibitor to cultured metanephroi impaired cell proliferation and nephrogenesis (9).…”
Section: Sapk In Renal Physiologymentioning
confidence: 99%